The use of technological tools o effectively manage virtual language courses - Cruz Grijalva, Milton Rogelio; Pleitez Aguilar, Irvin Efrain (2024)
One of the major consequences of our response to the COVID-19 pandemic has been a disruption to traditional classroom learning and instruction. A national health emergency forced teachers to move online, and although educators had more time to plan for online and hybrid classes, they faced many unknowns: changing rates of infection, chaotic decision-making, and more. Most schools have continued to organize teachers and students in class groupings and follow modified school schedules, trying to replicate traditional teacher and student interactions in virtual platforms like Google Meet or Zoom. For future graduates to be better prepared, the University of El Salvador looked for alternatives to facilitate the tools to effectively manage virtual classes. Through this course, future graduates have been provided with several tools to teach and learn a foreign language in a virtual classroom; the course is made up of three modules covering the fundamentals of online education, its application on the English Language Teaching, theoretical fundamentals and the use of technological tools for teaching-learning a foreign language in a virtual modality. The purpose of this report is to empower future graduates to create and deliver effective virtual lessons.